Adsorptive removal of phosphate and nitrate by layered double hydroxides through the memory effect and in situ synthesis - Sarah Mariska; Zhang Jin-Wei; Hoang Huu Chien; Duong Minh Ngoc; Nguyen Duy Hai; Huan-Ping Chao (Applied Water Science)
Abstract This research examines the efficacy of layered double hydroxides (LDHs) in removing phosphate and nitrate from wastewater, enhanced by the memory effect and in situsynthesis techniques. LDHs were synthesized hydrothermally, initially creating carbonate-based CO₃–LDHs, which were then converted to chloride-based Cl–LDHs through anion exchange. These LDHs underwent calcination at 300 °C, 400 °C, and 500 °C to optimize their structure for enhanced adsorption capabilities. The synthesized LDHs were thoroughly characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Brunauer–Emmett–Teller (BET) surface area analysis, and X-ray diffraction (XRD). Adsorption experiments in solutions with pH values between 5, 7, and 9 revealed the adsorption capacities of phosphate and nitrate on the CO₃–LDHs and Cl–LDH, respectively. The results indicated that LDHs calcined at 500 °C showed the highest adsorption performance, achieving maximum capacities of 184 mg/g for phosphate and 70.1 mg/g for nitrate. Kinetic studies confirmed that the adsorption process followed a pseudo-second-order model, demonstrating the effectiveness of the memory effect in enhancing ion exchange. The in situ synthesis of LDHs under controlled conditions significantly improved the removal rates of these anionic contaminants from wastewater, proving the potential of this method for the realistic wastewater treatment.